It takes a village: Community science informs tick encounter, pathogen, and exposure risk in North Carolina, USA - Dayvion R. Adams; Kane Lawhorn; Allison N. Yackley; Kaylin S. Lewandowski; Martha O. Burford Reiskind; Alexis M. Barbarin; Michael H. Reiskind (PLoS ONE, 2026)
As tick-borne disease cases continue to increase over time, there is a growing need to understand the ecological and epidemiological factors that contribute to disease risk. North Carolina is currently experiencing a rise in cases, yet tick-borne research in the state remains limited. In this study, we developed a framework for a community science program in collaboration with 22 county public health agencies to recruit participants to submit incidentally encountered ticks. As part of kit submissions, participants also completed a form describing where and when they encountered the tick, as well as the behaviors that led to the encounters. Submitted ticks were tested for several putative bacterial pathogens, including Borrelia burgdorferi , Ehrlichia spp., and Rickettsia amblyommatis . We additionally assessed how advertising methodology and frequency by county health agencies influenced tick kit submissions and evaluated correlations between agency perceptions of project performance and submission rates. Over two years, we received 444 ticks across 319 unique submissions. While species distributions were largely consistent with prior observations, we report the first published instance of Amblyomma americanum within the mountainous region of NC, indicating a potential range expansion into cooler, higher-altitude areas. Relative risk modeling identified recreational activities as consistently associated with higher likelihood of tick kit submissions. Multiple advertising types appeared to influence the number of kits submitted; however, these results should be interpreted cautiously due to small sample sizes. Overall, our study demonstrates a successful collaboration with state and county health agencies to engage the community in tick-borne disease research. Future studies should build on this framework to further optimize participation.